HQ CAR IS A NEW W VIR TYPE STAR - Udovichenko, S. N.; Kovtyukh, V. V.; Egorova, I. A.; Belik, S. I. (Одеські астрономічні публікації, 2013)
HQ Car is listed as an δ Cep star (DCEP) in the GCVS. High-resolution spectra of HQ Car showed the presence of the Balmer and HeI 5876 Å emissions. The light curve shows steeper rise than decline, and there is evidence for the presence of a bump in the descending branch around the phase of 0.4. From considerations of the period, spectral type, presence of the bump, Helium and Balmer emissions we conclude that HQ Car belongs to the W Vir class of Type II Cepheids